Magnetic resonance imaging findings of patients with intracranial tuberculoma in a private center in Lima, Peru - Castro-Magluff, Conrado (2023)
One of the forms of the inflammatory-infectious condition of tuberculosis, which is a major public health problem in the countries of Latin America, Asia and Africa with potential worldwide spread, is the parenchymal tumor form in the brain, known as tuberculous granuloma or tuberculoma. This form commonly causes mass effect and perilesional edema, which are often confused with the radiological manifestations of other granulomas and neoplastic masses, especially high-grade ones. Therefore, it is necessary to carefully study it using clinical and epidemiological knowledge, laboratory tests and, above all, magnetic resonance imaging. In this article, we share some imaging observations of proven cases of tuberculous granulomas in the brain, examined in a private MRI diagnostic radiological center. That could help in the diagnosis, thus avoiding the progression of the disease with its known consequences and the use of invasive methods.